P36 Comparison of glue and onyx for embolization of non-cavernous cranial dural arteriovenous fistulas. (29th August 2022) - Lynch, J; Dobrocky, T; Mansoor, N; Hendricks, E; Nicholson, P; Radovanovic, I; terBrugge, K; Pereira, VM; Agid, R; Krings, T
Abstract : Introduction: Cranial dural arteriovenous fistulas (DAVF) are arteriovenous shunts involving the dural venous sinuses or cortical veins. Endovascular treatment may be achieved via transarterial or transvenous use of liquid embolics and/or coil deployment. The most commonly used liquid embolic agents to date are n-butyl-2-cyanoacrylate (n-BCA) and Onyx. 1, 2 Aims of study: Evaluate the safety and efficacy of n-BCA versus Onyx for the safety and efficacy of endovascular treatment of DAVFs. Methods: A retrospective review of an institutional PACS database was performed to identify patients who underwent first-line endovascular embolization of intracranial DAVF at our institution from January 2009 to December 2019 using n-BCA or Onyx. Treatments employing adjunctive usage of coils were included. Follow-up was with clinic attendance, digital subtraction angiography in addition to cross-sectional imaging (primarily MRI). Results: A total of 79 patients underwent first-attempt embolization procedures between January 2009 through December 2019. 32 patients underwent embolization with n-BCA and 47 patients with Onyx. 16 out of 32 (50%) DAVFs treated with n-BCA and 38 out of 47 (80.9%) DAVFs treated with Onyx achieved angiographic occlusion of the fistula at time of procedure. This difference was statistically significant (p=0.006). In this group there were no recurrences at follow-up (average 40 months). Adverse events were slightly less in the Onyx group but the difference was not statistically significant. Conclusions: We have demonstrated, in this retrospective series, that Onyx has greater treatment efficacy for occluding non-cavernous DAVF. The safety profile of Onyx does not appear inferior to that of n-BCA. References: Rezende MTS, Piotin M, Mounayer C, Spelle L, Abud DG, Moret J. Dural arteriovenous fistula of the lesser sphenoid wing region treated with onyx: technical note. Neuroradiology . 2006;48 (2):130–134. Doi:10.1007/S00234-005-0020-9 Cognard C, Januel AC, Silva NA, Tall P. Endovascular treatment of intracranial dural arteriovenous fistulas with cortical venous drainage: new management using onyx. AJNR AM J Neuroradiol . 2008;29 (2):235–241. DOI:10.3174/AJNR.A0817 Do you have any conflict of interest to declare? : No